Peran Pemberian Terapi Latihan Pasca Operasi Total Knee Arthroplasty pada Kasus Osteoarthritis : Artikel Review - Andrew Wijaya Saputra (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2021)
Introduction: Damage to cartilage can be caused by various factors, the most common of which is osteoarthritis. Total Knee Arthroplasty (TKA) is a surgical procedure applied to replace the knee joint area using fixed bearing implants. This surgery has a high success rate and can improve knee function and quality of life. Objective: to examine the role of physiotherapy in reducing the risk of TKA complications such as pain, swelling and decreased motor function. Methods: literature review by searching the website of the National Center for Biotechnology Information. Results: Exercise therapy interventions that can be used for TKA include ROM exercises, stretching exercises, strengthening exercise, stability exercise, balance exercise, and functional exercises. Conclusion: The role of physiotherapy by providing exercise therapy in post-TKA can be useful to reduce pain and improve function, movement and quality of life.